2017
DOI: 10.15253/2175-6783.2017000100005
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric nurse´s work process: a reality to be transformed

Abstract: Objective: to analyze the work process of the pediatric nurse, focusing on the hospitalized child. Methods: this is a qualitative research with 17 nurses of a university public hospital, performed by semi-structured interview and participant observation. The analysis of the data content was based on the referential of the work process in health. Results: the actions of the pediatric nurse indicate that their work is far from the planning of integral and humanized care for the children. It is developed from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
2
1
6
Order By: Relevance
“…The data found in this study diverged from other scientific evidence that showed the existence of vertical relations and power among workers in the work of nurses in pediatrics (17) , which goes in the opposite direction to the cooperation and aggregation of the collective. In this way, the relationship between workers is essential for social relationships since besides strengthening affective bonds, it also stimulates and fosters communication, enabling reflection and critical positioning of workers, developing creativity and harmonization teams.…”
Section: Discussioncontrasting
confidence: 99%
“…The data found in this study diverged from other scientific evidence that showed the existence of vertical relations and power among workers in the work of nurses in pediatrics (17) , which goes in the opposite direction to the cooperation and aggregation of the collective. In this way, the relationship between workers is essential for social relationships since besides strengthening affective bonds, it also stimulates and fosters communication, enabling reflection and critical positioning of workers, developing creativity and harmonization teams.…”
Section: Discussioncontrasting
confidence: 99%
“…The analyzes revealed how broad the motivation for training is, at the beginning of the trajectory, broad and connected to the objective of achieving competencies to work in the specialty and provide good care, based on their understanding of it. It is the development of procedural skills that values the intensive care clinic and can be attributed to the environment and care model characteristic of the NICU, which emerged with a focus on ensuring survival of premature new-borns (PTNB) or those with other conditions (2,(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…Para que a equipe proporcione medidas de conforto e ações menos traumáticas com tranquilidade e segurança, é necessário que reconheçam seus próprios sentimentos, em relação aos pacientes com necessidades especiais de saúde, a fim de estarem em plenas condições para compreender as emoções vivenciadas, estabelecendo relação empática com a família e o paciente (Terezam et al 2016;Soares et al 2020). Research, Society andDevelopment, v. 10, n. 3, e15010313054, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i3.13054 Muitos profissionais, durante seu cotidiano de trabalho, mostram-se atentos às necessidades de cada criança ou adolescente, ao cuidado humanizado e à hospitalização não traumática (Leite et al 2017). O cuidado de criança e/ou adolescente com necessidade especial de saúde deve estar centrado na família, principalmente na figura materna (Meirelles Leite et al 2019).…”
Section: Discussionunclassified